2014
DOI: 10.1186/1477-7827-12-10
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine profile following stimulation with recombinant follicle stimulating hormone and luteinizing hormone versus highly purified human menopausal gonadotropin

Abstract: BackgroundLuteinizing hormone (LH) activity in human menopausal gonadotropin (hMG) preparations is derived from human chorionic gonadotropin (hCG) rather than LH. Therefore, we aimed to determine whether there are similarities in the endocrine and follicular profiles of serum and follicular fluid from controlled ovarian stimulation with the recombinant gonadotropins follicle-stimulating hormone plus luteinizing hormone (rFSH + rLH) or highly purified human menopausal gonadotropin (HP-hMG).MethodsWe performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…According to the “two‐cell, two‐gonadotropin” theory, LH might lead to the synthesis of progesterone and dehydroepiandrosterone sulphate, which are precursors of oestrogen, thus leading to a negative feedback regulation of LH level. Although study on hMG vs recombinant FSH + recombinant LH demonstrated similar hormone profiles for both groups, small variations in steroid hormones are difficult to capture using blood samples. Moreover, the pregnancy rate in this study was higher than the rates in other studies, as most of the participants were young and nearly 80% of these women had not experienced IVF failure.…”
Section: Discussionmentioning
confidence: 99%
“…According to the “two‐cell, two‐gonadotropin” theory, LH might lead to the synthesis of progesterone and dehydroepiandrosterone sulphate, which are precursors of oestrogen, thus leading to a negative feedback regulation of LH level. Although study on hMG vs recombinant FSH + recombinant LH demonstrated similar hormone profiles for both groups, small variations in steroid hormones are difficult to capture using blood samples. Moreover, the pregnancy rate in this study was higher than the rates in other studies, as most of the participants were young and nearly 80% of these women had not experienced IVF failure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, quantifying the precise biological activity of gonadotropins was difficult. However, Requena [16] reported that endocrine and follicular profiles were not different between rFSH + rLH and hp-hMG stimulation and previous studies also compared hMG with uFSH [5, 11, 14, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…It seems, however, that a daily bolus of rLH is still sufficient, despite its short half-life, to boost steroidogenesis and, in particular, oestradiol to levels similar to those induced by a daily bolus of rHCG. Over the years, studies have compared different low-dose HCG or rLH supplementation regimens with FSH stimulation (Drakakis et al, 2009;Kilani et al, 2003;Requena et al, 2014;Thuesen et al, 2012;Van Horne et al, 2007). Therefore, Van Horne et al (2007) retrospectively analysed the outcomes of 190 cycles in which either rFSH alone or rFSH supplemented with uHCG (50-100 IU) daily were used for ovarian stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators reported that the number of follicles, oocytes and transferable embryos as well as the clinical pregnancy rate were significantly higher in the HCG group. In a more recent study, Requena et al (2014) compared the steroid profile after stimulation with rFSH and rLH versus HMG in 50 oocyte donors. Both groups had a FSH:LH activity ratio of 2:1 and the LH bioactivity ratio was 1:1.…”
Section: Discussionmentioning
confidence: 99%